The Sami Representations Reflecting the Multi-Ethnic North of the Saga Literature - Aalto, Sirpa; Lehtola, Veli-Pekka (Journal of Northern Studies, 2018)
This article focuses on contextualizing the Sami (finnar) representations in Old Norse saga literature. The purpose is to show that the Sami representations reflect multi-layered Old Norse textual and oral traditions, and complex interaction between the Sami and the Norwegians in the Middle Ages. The stereotypes of the Sami tell us more about the society that created them than about real, historical events. We can be sure that behind them lie very mundane phenomena such as trade and marriages. The ultimate goal of the article is therefore to reveal the multi-ethnic North that provided the background for the saga sources, a North whose history is not as homogeneous as sources suggest and quite unlike the modified version which found its way into the histories of nation states. The literary conventions of sagas are not just imaginary tales—their use in various contexts can reveal something essential in otherwise schematic images or configurations. Even researchers of the sagas have certain personal conceptions of what the “real” lives of the Sami were like at the time, and how the sagas depict this. In fact, they participate in a continuum of saga literature that generates representations of the Sami in history.